Valid virtual reality applications for commercial kitchen safety training - Saad, Mazni; Mohamad Najib, Muhammad Danial Haiqal; Thomas, James Pratt; Nazir, Faridah (e-International Publishing House, Ltd., UK, 2022)
The rise in the number of workers in gastronomy tourism has coincided with an increase in workplace accidents. New workers lack hazard identification abilities and fail to recognize dangerous events in the workplace. Thus, a two-fold goal has been established: (1) design and develop VR applications for spotting risks in the kitchen workplace, and (2) validate the VR application's effectiveness. The invention involved the 360-degree camera and VR software, and it was validated by multiple experts who had long working experience. The VR technology was found noteworthy as it received positive acceptance in the hospitality business.